2016
DOI: 10.1038/srep39453
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation Directly Induces Fold Destabilization of Proteins

Abstract: Ubiquitin is a common post-translational modifier and its conjugation is a key signal for proteolysis by the proteasome. Because the molecular mass of ubiquitin is larger than that of other modifiers such as phosphate, acetyl, or methyl groups, ubiquitylation not only influences biochemical signaling, but also may exert physical effects on its substrate proteins by increasing molecular volume and altering shape anisotropy. Here we show that ubiquitylation destabilizes the fold of two proteins, FKBP12 and FABP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 31 publications
0
34
0
1
Order By: Relevance
“…Our results clearly show that ubiquitin can affect a protein's energy landscape with consequences for proteasomal degradation. There are no clear patterns regarding the region or type of secondary structure within the substrate that is energetically sensitive to the attachment of ubiquitin, nor are the effects correlated with the substrate size, as previously suggested 27 . It is reasonable to expect that the addition of a protein domain, such as ubiquitin, can alter the energetics and dynamics of a target protein in this manner.…”
Section: Discussionmentioning
confidence: 64%
“…Our results clearly show that ubiquitin can affect a protein's energy landscape with consequences for proteasomal degradation. There are no clear patterns regarding the region or type of secondary structure within the substrate that is energetically sensitive to the attachment of ubiquitin, nor are the effects correlated with the substrate size, as previously suggested 27 . It is reasonable to expect that the addition of a protein domain, such as ubiquitin, can alter the energetics and dynamics of a target protein in this manner.…”
Section: Discussionmentioning
confidence: 64%
“…Human ubiquitin G76C was expressed in Escherichia coli strain BL21 ( DE3 ) in LB media (Nacalai Tesque) or M9 minimal media containing 99% 15 N-labeled ammonium chloride (Cambridge Isotope Laboratories); for the triple-resonance NMR experiments, the M9 medium also contained 99% U- 13 C-labeled D-glucose (Cambridge Isotope Laboratories). The ubiquitin mutant was purified as described previously 5 . Protein purity was checked by SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that the thermodynamic stability of ubiquitin decreases with polymerization, and that polyubiquitin forms amyloid-like fibrils when heat or shear stress is applied 2 . In addition, we recently found that the covalent conjugation of ubiquitin molecules (ubiquitylation) to proteins induces structural fluctuations, resulting in a decreased in thermodynamic stability 5 . Thus, the formation of an (iso-)peptide bond between ubiquitin units in polyubiquitin seems to markedly alter the physicochemical properties of the ubiquitin molecules, leading to the production of amyloid-like fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…How could we explain the ability of conjugated SUMO to increase the aggregation of disease-causing proteins? One possibility is that proteins involved in neurodegenerative diseases are intrinsically prone to aggregation and that different PTMs with some hydrophobic character would more easily tilt the equilibrium toward their aggregation ( O’Rourke et al, 2013 ; Morimoto et al, 2016 ). Another possibility is that excessive SUMOylation at multiple lysine residues, due to enhanced SUMOylation machinery upon aging and stress ( Tempe et al, 2008 ; Scurr et al, 2017 ; Henley et al, 2018 ), could trigger the aggregation of crucial proteins in different neurodegenerative diseases.…”
Section: Sumoylation and α-Synuclein Aggregationmentioning
confidence: 99%